Trends in immediate breast reconstruction and radiation after mastectomy: A population study. Issue 3 (17th September 2019) - Doherty, Christopher; Pearce, Sabrina; Baxter, Nancy; Knowles, Sarah; Ross, Douglas; McClure, J. Andrew; Brackstone, Muriel
Abstract: In the last decade, there has been an increase in women undergoing immediate breast reconstruction (IBR) at the time of mastectomy. Recent literature suggests a shift in practice: Surgeons are becoming more comfortable with IBR in the setting of possible postoperative adjuvant radiotherapy, despite the known complications. This study sought to investigate, at a population level, the patient and surgeon characteristics associated with the use of IBR and which of these factors were predictive of adjuvant radiotherapy. This retrospective population‐based cohort study included all adult women who underwent mastectomy in the province of Ontario from 2007 to 2014. The Canadian Institute for Health Information (CIHI) administrative data base was used to generate patient demographic and clinical data. The Ontario Health Insurance Plan (OHIP) data base was used to elicit surgeon characteristics including clinical experience and volume of practice dedicated to breast surgery. Outcome variables included reconstruction concurrent with mastectomy, alloplastic vs autologous reconstruction, and use of radiation. A total of 25 861 patients underwent mastectomy and 2972 had IBR (11.5%). The rate of IBR after mastectomy increased over time from 7.2% in 2007 to 17.2% in 2014 ( P  < .001). There was also an increase in the proportion of patients with IBR who received radiation over the time period, from 19.4% in 2007 to 28.2% in 2014 ( P  = .003). In the first regression analysis, IBR was associated with younger patient age, residing in closer proximity to cancer clinics, absence of malignant breast disease (ie, prophylactic mastectomy), having a younger surgeon performing the mastectomy, and receiving care at a teaching hospital. A second analysis showed that patient variables predictive of radiation after IBR were a younger age and a more advanced cancer stage and no variables specific to surgeon or institution were predictive of radiation in patients with IBR. A significant increase in the rate of IBR as well as the use of radiation occurred over the 7‐year study period. Multiple patient and surgeon factors were associated with IBR. Variables associated with radiation in IBR were harder to predict. Given the increase in the use of radiation in IBR, further research is needed to look at long‐term outcomes in these patients at the population level.